CircularMAT: Materials Advisor Tool to promote circular material selection in fashion design - Mazzitelli, Melissa; Papile, Flavia; Del Curto, Barbara (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
Discussing fashion entails revisiting history through both individual and collective expressions. However, the narrower meaning traditionally associated with the term has, for centuries, referred to the replacement of the old with the new — something that better reflects the Zeitgeist. By embracing the spirit of the time, fashion has evolved in response to today’s uncertain future and precarious environmental conditions, moving beyond impulsive opulence toward sustainability. The sector may now be prepared to adopt a new definition of fashion as something not transient, but rather enduring. Durability is a cornerstone of the circular economy model, which seeks to keep materials and products in regenerative production cycles for as long as possible. In this context, the present paper introduces CircularMAT, a practical material advisory tool developed to support fashion designers in selecting materials that promote durability and enable circular design strategies. CircularMAT offers a structured system for material exploration, providing comprehensive information on traditional, preferred, and emerging materials. It links material characteristics to core principles of circular fashion and maps them against design strategies intended to extend product lifecycles and reduce environmental impact. The tool is designed to integrate seamlessly into the designer’s workflow, fostering conscious and informed material selection decisions during the early stages of the creative process. By emphasizing the relationship between material properties, durability, and circularity, CircularMAT supports the adoption of more sustainable design practices — without compromising creativity.